2017
DOI: 10.25175/jrd/2017/v36/i2/116407
|View full text |Cite
|
Sign up to set email alerts
|

Direct Vs Indirect Election to Grama Panchayat President: Reflections and Implications

Abstract: This discussion paper is a qualitative analysis built on opinions. Though there is no one-to-one link between performance and service delivery of grama panchayats (GPs) and method of election to GP president, the paper talks about opinions, which support direct election. There is a discussion going on at the policy level in States like Karnataka whether to go in for direct election of the president of the gram panchayat or not. Although the overall preference of stakeholders and people is for direct election, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Direct election of chairpersons was also perceived as more efficacious in restricting capture of power by local elites. Sivanna et al (2017) also found that the exercise of the right to recall (via a noconfidence motion, or NCM) was significantly more frequent in respect of indirectly elected chairpersons. This paper will later explore the incidence of NCMs in UP in some detail.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Direct election of chairpersons was also perceived as more efficacious in restricting capture of power by local elites. Sivanna et al (2017) also found that the exercise of the right to recall (via a noconfidence motion, or NCM) was significantly more frequent in respect of indirectly elected chairpersons. This paper will later explore the incidence of NCMs in UP in some detail.…”
Section: Introductionmentioning
confidence: 81%
“…The authors therefore urge that the legislative intent of the enabling Act for women's quotas in PRIs should be more diligently put into practice. This paper has already noted that direct elections to the post of ZPAs in other states of India lead to higher satisfaction among the people with the functioning of the ZP when compared to indirect election (Sivanna et al 2017). The logistics of conducting direct elections for ZPAs in UP are not too onerous, as evidenced by current practice in the two lower levels of PRIs, which already fill the positions of both ZP members and ZPAs by direct election.…”
Section: Declaration Of Conflicting Interestmentioning
confidence: 92%